Pediatric Rheumatology Curriculum for the Pediatrics Resident: A Case-Based Approach to Learning - Miriah Gillispie; Eyal Muscal; Jennifer Rama; Carla Falco; Amanda Brown (Association of American Medical Colleges, 2018)
Introduction Pediatric rheumatologic disease occurs more frequently than several other chronic pediatric diseases but is often underrecognized. It is estimated that in the US, one in 250 children has some form of juvenile arthritis and 300,000 children have a form of rheumatologic disease. However, there are only approximately 400 practicing pediatric rheumatologists nationwide. Methods Kern's six-step method was used to develop a pediatric rheumatology curriculum based on respondents' perceived lack of training and comfort with four key areas: workup, musculoskeletal exam, laboratory interpretation, and referral to rheumatology. These cases were developed for second-year pediatric and second- and third-year internal medicine-pediatric residents rotating with the service. The curriculum was composed of four 30-minute case discussions as well as an observed musculoskeletal exam session. Results In 2017, weekly case study sessions reached 34 trainees. Survey results from these trainees are representative of our overall results and reveal that learners felt the content of the cases helped increase comfort with compiling pertinent history and information of symptoms consistent with autoimmune disease, recognizing physical exam findings of autoimmune disease, ordering and interpreting laboratory studies in children with concerns for autoimmune disease, and referring to pediatric rheumatology. Discussion This case-based curriculum exposed residents to presentations of the more common autoimmune diseases encountered in the pediatric population. The curriculum helps fill a gap in pediatric training through increased exposure to this subset of chronic diseases and expands physical examination skills not typically taught in general pediatrics.